2-deoxy-2[F-18] fluoro-D-glucose positron emission tomography Deauville scale and core-needle biopsy to determine successful management after six doxorubicin, bleomycin, vinblastine and dacarbazine cycles in advanced-stage Hodgkin lymphoma. (June 2020) - Picardi, M.; Fonti, R.; Della Pepa, R.; Giordano, C.; Pugliese, N.; Nicolai, E.; Salvatore, M.; Mainolfi, C.; Venetucci, P.; Rascato, M.G.; Cappuccio, I.; Mascolo, M.; et al.
Abstract: Background: The clinical impact of the positivity of the Deauville scale (DS) of positron emission tomography (PET) performed at the end of doxorubicin, bleomycin, vinblastine and dacarbazine (ABVD) in patients with advanced Hodgkin lymphoma (HL), in terms of providing rationale to shift poor responders onto a more intensive regimen, remain to be validated by histopathology. Patients and methods: This prospective trial involved patients with stage IIB/IV HL who after six ABVD cycles underwent PET (PET6) and core-needle cutting biopsy (CNCB) of 2-deoxy-2[F-18] fluoro-d -glucose (FDG)-avid lymph nodes. Patients received high-dose chemotherapy/autologous haematopoietic stem cell rescue (HDCT/AHSCR) if CNCB was positive for HL, alternatively, if CNCB or PET was negative, received observation or consolidation radiotherapy (cRT) on residual nodal masses, as initially planned. The end-point was 5-year progression-free survival (PFS). Results: In all, 43 of the 169 (25%) evaluable patients were PET6 positive (DS 4, 32; DS 5, 11). Among them, histology showed malignancy (HL) in 100% of DS 5 scores and in 12.5% of DS 4 scores. Fifteen patients with positive biopsy received HDCT/AHSCR, whereas 28 patients with negative biopsy, as well as 126 patients with negative PET6, continued the original plan (cRT, 78 patients; observation, 76 patients). The 5-year PFS in the negative PET6 group, negative biopsy group and positive biopsy group was 95.4%, 100% and 52.5%, respectively. Conclusion: DS positivity of end-of-ABVD PET in advanced HL carried a certain number of CNCB-proven non-malignant FDG-uptakes. The DS 4 scores which were found to have negative histology appeared to benefit from continuing the original non-intensive therapeutic plane as indicated by the successful outcome in more than 95% of them by obtaining similar 5-year PFS to the PET6-negative group. By contrast, the DS 5 score had consistently positive histology and was associated with unsuccessful conventional therapy, promptly requiring treatment intensification or innovative therapeutic approaches. Highlights: Deauville score (DS) 4 at the end-of-ABVD FDG-PET in advanced Hodgkin lymphoma (HL) had a rate of negative-histology of 87.5%. DS 5 score at the end-of-ABVD FDG-PET in advanced HL had a rate of positive-histology of 100%. Histology is needed to confirm malignancy for DS 4 scores at restaging PET. Switch to treatment intensification or innovative therapeutic approach as soon as possible for DS 5 score at restaging PET.